Implementación del mantenimiento predictivo al tambor rotatorio de tapas corona. (2023)
Maintenance has been a major issue from the beginning of industries to our time because represents greater or lesser economic benefits for the industries. For this reason, maintenance will be implemented predictive in a rotary tapas drum of the “corona” brand, the which has the function of separating material that does not comply with certain quality conditions, which in this case are the tapas "crown" mark that are deformed and sheared.